The politics of excellence : behind the Nobel Prize in science - Friedman, Robert Marc, 1949- (New York : Times Books, 2001)
Presents a behind-the-scenes look at the history of the Nobel Prize, awarded for achievement in physics and chemistry, drawing from official unpublished documents and private correspondence to support the author's charge that excellence is not always rewarded and that there are other, less noble reasons why some individuals have won.
"A W. H. Freeman book.".
Includes bibliographical references and index.
Kirkus Review.
Library Journal.
Adult
Keywords: Chemistry -- Awards -- History; Nobel Prizes -- History; Physics -- Awards -- History; Chemistry -- Awards -- History; Nobel Prizes -- History; Physics -- Awards -- History